2012
DOI: 10.1177/0009922812441671
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Telepsychiatry Consultation Practice in Rural Georgia for Primary Care Physicians

Abstract: Establishing a child telepsychiatry consultation practice is feasible in rural areas. This report describes the benefits and challenges of our telepsychiatry consultation clinic with rural pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Two studies conceptualized parent satisfaction as a factor in testing the feasibility of implementation of an intervention [ 57 , 71 ]. Two telemedicine studies specifically defined satisfaction with relation to technology functioning and comfort, and timely and geographic access to care [ 47 , 59 ]. Two studies examined treatment satisfaction with different components of multidisciplinary teams that worked with their child [ 16 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies conceptualized parent satisfaction as a factor in testing the feasibility of implementation of an intervention [ 57 , 71 ]. Two telemedicine studies specifically defined satisfaction with relation to technology functioning and comfort, and timely and geographic access to care [ 47 , 59 ]. Two studies examined treatment satisfaction with different components of multidisciplinary teams that worked with their child [ 16 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…13 The existing studies on telebehavioral health among rural children have limitations of being outdated 17 or being limited to small settings. 18 We address this gap in the literature by using a representative sample from 15 school-based telehealth programs from across the United States. The purpose of this paper is to explore the use of school-based telebehavioral health care to address the access needs of children and adolescents, especially in rural communities.…”
Section: The Role Of School-based Telehealth To Address Behavioral He...mentioning
confidence: 99%
“…Researchers and providers have been advocating for the use of telebehavioral health care in various settings for years, but research literature on the effectiveness of such models among rural children is limited 13 . The existing studies on telebehavioral health among rural children have limitations of being outdated 17 or being limited to small settings 18 . We address this gap in the literature by using a representative sample from 15 school‐based telehealth programs from across the United States.…”
Section: Barriers To Behavioral Health Treatment For Children and Ado...mentioning
confidence: 99%
“…In the context of public health, others have highlighted telehealth as a way for patients to maintain human connection during social distancing and lockdowns ( Whaibeh et al, 2020 ). Findings are mixed with respect to patient satisfaction of psychiatric telehealth services ( Frueh et al, 2005 ; Jacob et al, 2012 ; Nelson et al, 2003 ; Ruskin et al, 2004 ; Zimmerman et al, 2021a ), yet remote care has been shown to improve access to mental health treatment in some cases, especially for individuals experiencing linguistic or financial obstacles ( Chong and Moreno, 2012 ; Moreno et al, 2012 ; Mucic 2010 ; Ye et al, 2012 ). For example, Mucic (2010) highlights that the availability of bilingual clinicians through remote care can help overcome travel requirements for both patients and providers, as well as lead to higher patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%